Hepatitis B virus infection among pregnant women in Ethiopia: a systematic review and Meta-analysis of prevalence studies - Kebede, Kindie Mitiku (BMC Infect Dis, 2018)
BACKGROUND: There are several epidemiological studies available on hepatitis B virus among pregnant women in Ethiopia. These individual studies revealed wide variation over time and across geographical areas. The aim of this systematic review and Meta-analysis is to estimate the overall prevalence of hepatitis B virus infection among pregnant women in Ethiopia. METHODS: A comprehensive search of electronic databases including PubMed, Popline, Lalicus, Ovid, MedNar, African Journal Online (AJOL) and advanced Google Scholar was conducted regardless of publication year from August 30, 2017 to September 25, 2017. The search was updated on January 02, 2018 to minimize time-lag bias. The methodological qualities of included studies were assessed using Joanna Briggs Institute Meta-Analysis of Statistics Assessment and Review Instruments. RESULTS: Out of 103 studies, 17 studies with a total of 5629 pregnant women were included in the Meta-analysis. The pooled prevalence of hepatitis B virus infection among pregnant women using random-effect model was 4.7%(95% CI 4.0–5.4%). The I(2) statistics was I(2) = 37.9%(p = 0.0575). Even though significant heterogeneity among studies was not detected, the I(2) = 37.9% suggests medium heterogeneity. A subgroup Meta-analysis showed that study site, region, mean/median sample size, hepatitis B virus screening methods and methodological quality were not source of heterogeneity (p-difference > 0.05). CONCLUSION: This review shows an intermediate level of hepatitis B virus infection among pregnant women in Ethiopia. In addition to the current practice of child vaccination, routine and universal antenatal hepatitis B virus screening program need to be implemented. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12879-018-3234-2) contains supplementary material, which is available to authorized users.